PENGARUH PEMBERIAN MAKANAN TAMBAHAN PEMULIHAN (PMT-P) TERHADAP PERUBAHAN STATUS GIZI BALITA GIZI BURUK TAHUN 2017 ( Studi di Rumah Gizi Kota Semarang) - Imas Rini; Dina Rahayuning Pangestuti; M. Zen Rahfiludin (Jurnal Kesehatan Masyarakat (Undip), 2017)
Severe acute malnutrition is a problem of nutrient deficiency determined based on weight indicator according to height (WHZ) with Z-score  <-3 SD with the presence or absence of edema. Suplementary foods is one of the activities in the effort to resolve malnourished children under five in Semarang City.The purpose of this research is to analyze the effect of supplementary foods to nutritional status change of malnourished children in Nutrition House of Semarang City. The type of research used is quasi-experimental with one group design pretest posttest design where the design is no control group. The population of this study were all children who followed intensive care in Nutrition House and using non probability sampling technique with purposive sampling method. Anthropometric measurements were performed before and after suplementary food interventions, recording of infectious diseases and comorbidities during supplementary foods interventions and recall consumption of energy and protein of foods other than supplementary foods. After the research, it was found that the change of anthropometric status of children according to weight for height  index of 12 under five children which is very thin 4 children got a change of nutritional status to 3 children of thin category and 1 child of normal category. The anthropometry index of weight for age indicates that there is a change of anthropometric status of children which is 1 child becomes undernutrition and 11 others are still in severe acute malnutrition category. The results showed that there was a difference of anthropometric status of index of Weight for Age (WAZ) before and after supplementary  foods and  anthropometry index of Weight for Height (WHZ) there was no significant difference of nutritional status of children under five before and after of suplementary foods.